Exploring the Maxims of Filipino Kanal (canal) Humour through Semantic Analysis - Abegail Baring; Betty Mae Albia; Angelie Guevarra; John Jonathan N Normandia; Ruel Bonganciso (Advanced Qualitative Research, 2025)
This study aims to systematically and semantically analyze kanal humour in conversation– its feature, the meaning behind it, as well as what it conveys or expresses to give clarifications and a more profound understanding of kanal humour. This study used the Semantic Analysis method to analyze and interpret the content of Kanal humour in Tiktok videos. Furthermore, the result shows that kanal humour uses specific linguistic strategies, such as homophonic puns and double entendres, and violates maxims of conversations to subvert expectations and entertain. The analysis of "kanal humor" supports current theories of humor, showing that reinterpreting word meanings creates humor through incongruity and the subversion of expectations. Furthermore, the study shows how this form of humour has influenced language use among TikTok users, creating a distinct linguistic style that may be vague to those outside the platform's community. This effect is consistent with studies of language and communication, which show that humour often stems from typical conversational patterns. Researchers recommend that this study is of use as a reference for future researchers that would also study kanal humour across various social media platforms such as Instagram, Facebook, X, etc., as well as to examine and compare the content of Kanal humour from these platforms. Lastly, this can be of use or contribute to the field of linguistics and digital communication.